Hybrid Nanocomposites Based on Graphene and Its Derivatives: From Preparation to Applications - Ansa, Kanwal; Asim Ali, Yaqoob; Affia, Siddique; Showkat, Ahmad Bhawani; Mohammad Nasir, bin Mohammad Ibrahim; Khalid, Umar (Springer, 2021)
Graphene has obtained an excessive amount of interest and popularity from worldwide owing to its atypical physiochemical, chemical, thermal and mechanical stability-based properties. Graphene, a one atom thick plain sheet with sp2 bonding and the carbon atoms are compactly packed in structure to form crystal lattice. Many approaches are known to synthesize the graphene derivatives and therefore, it is essential to discuss a list of distinguished approaches like exfoliation and cleavage, thermal chemical vapor deposition etc. The most commonly used hybrid graphene nanocomposite synthesis approaches and their significant applications are also summarized in this chapter.